Assessment of the hilsa breeding ground in Meghna River estuary, Bangladesh for sustainable conservation - Md Anisur Rahman; Md Mehedi Hasan Pramanik; Md Monjurul Hasan; Flura; Rumana Yasmin; Yahia Mahmud (Academia Biology)
Hilsa, a significant fish species in Bangladesh, undergoes migratory patterns between the sea and rivers. This study, conducted from 2018 to 2020 in four locations (Ramnewaz, Hazirhat, Janata Bazar, and Sakuchia) along the River Meghna in Monpura, aimed to assess the effectiveness and reevaluate a previously identified hilsa breeding ground. Variations in plankton composition and abundance were observed over multiple years and locations within the estuary. The presence of plankton in the hilsa’s gut during the spawning season emphasized its importance in the fish’s diet. The research focused on the length-frequency distribution and length-weight relationship of hilsa larvae (Jatka), studying their abundance and dispersion during high and low tides. Positive allometric growth in Jatka suggested the breeding area’s good health. Additionally, the study monitored the spent rate and maturity stages of hilsa, demonstrating the effectiveness of conservation initiatives. The existing management strategy, safeguarding breeding grounds and sanctuaries, contributed to a consistent increase in the hilsa population. The satisfactory parameters observed in the Monpura hilsa breeding ground indicated its stable and ongoing functionality. Consequently, the research findings are essential evidence and a valuable reference for future studies, policies, strategies, and the sustainable management of hilsa fishery resources.